Face gender categorization and hemispheric asymmetries: Contrasting evidence from connected and disconnected brains. (17th December 2016) - Prete, Giulia; Fabri, Mara; Foschi, Nicoletta; Tommasi, Luca
Graphical abstract: Highlights: A split-brain patient and healthy controls were tested in a gender categorization task. Controls better categorized female/male faces in the left/right visual field (L/RVF). The patient was worse than the controls, except for male faces presented in the LVF. Abstract: We investigated hemispheric asymmetries in categorization of face gender by means of a divided visual field paradigm, in which female and male faces were presented unilaterally for 150 ms each. A group of 60 healthy participants (30 males) and a male split-brain patient (D.D.C.) were asked to categorize the gender of the stimuli. Healthy participants categorized male faces presented in the right visual field (RVF) better and faster than when presented in the left visual field (LVF), and female faces presented in the LVF than in the RVF, independently of the participants' sex. Surprisingly, the recognition rates of D.D.C. were at chance levels – and significantly lower than those of the healthy participants – for both female and male faces presented in the RVF, as well as for female faces presented in the LVF. His performance was higher than expected by chance – and did not differ from controls – only for male faces presented in the LVF. The residual right-hemispheric ability of the split-brain patient in categorizing male faces reveals an own-gender bias lateralized in the right hemisphere, in line with the rightward own-identity and own-age bias previously shown in split-brain patients. The gender-contingent hemispheric dominance found in healthy participants confirms the previously shown right-hemispheric superiority in recognizing female faces, and also reveals a left-hemispheric superiority in recognizing male faces, adding an important evidence of hemispheric imbalance in the field of face and gender perception.